Antibiotics Alter the Expression of Genes Related to Behavioral Development in Honey Bees (Hymenoptera: Apidae). Issue 2 (7th April 2022) - Ortiz-Alvarado, Yarira; Giray, Tugrul
Abstract: Honey bees, as many species of social insects, display a division of labor among colony members based on behavioral specializations related to age. Adult worker honey bees perform a series of tasks in the hive when they are young (such as brood care or nursing) and at ca. 2–3 wk of age, shift to foraging for nectar and pollen outside the hive. The transition to foraging involves changes in metabolism and neuroendocrine activities. These changes are associated with a suite of developmental genes. It was recently demonstrated that antibiotics influence behavioral development by accelerating or delaying the onset of foraging depending on timing of antibiotic exposure. To understand the mechanisms of these changes, we conducted a study on the effects of antibiotics on expression of candidate genes known to regulate behavioral development. We demonstrate a delay in the typical changes in gene expression over the lifetime of the individuals that were exposed to antibiotics during immature stage and adulthood. Additionally, we show an acceleration in the typical changes in gene expression on individuals that were expose to antibiotics only during immature stage. These results show that timing of antibiotic exposure alter the typical regulation of behavioral development by metabolic and neuroendocrine processes.